Pengembangan Media Pembelajaran IPAS Berbasis Articulate Storyline Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Negeri 16 Purwodadi Kabupaten Grobogan - Vrida Fitammami; Desi Wulandari (Journal of Classroom Action Research, 2026)
Abstract: This study aims to develop learning media based on Articulate Storyline on the material of the process of changing the state of matter in science learning and to determine its feasibility, practicality, and effectiveness in improving the learning outcomes of fourth-grade students of SD Negeri 16 Purwodadi. This study used the Research and Development (R&D) method with the Borg and Gall model. The research subjects consisted of fourth-grade students of SD Negeri 16 Purwodadi. Data collection techniques included pretest–posttest, questionnaires, observation, interviews, and documentation. The results showed that the developed media was declared very feasible with a validation percentage of media experts of 94.2% and material experts of 89.28%. The practicality of the media was demonstrated through teacher responses of 97.5% and students of 95.8% with a very good category. The media was proven to be effective in improving learning outcomes, indicated by the results of the paired t-test with a Sig. (2-tailed) value of 0.000 <0.05 and an N-Gain value of 0.7149 in the high category. Thus, Articulate Storyline-based learning media is feasible, practical, and effective for use in science learning in elementary schools.